The Influence of Promotions, Discounts, and Brand Trust on Impulsive Purchases of Fitbar Makassar - Charistantya Tegar Aganta; Metta Padmalia, Metta Padmalia; Teofilus, Teofilus (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study investigates the effect of promotional events and price discounts on impulse buying behavior among Fitbar consumers in Makassar City, with Brand Trust serving as an intervening variable. The research adopts the Stimulus-Organism-Response (S-O-R) framework to explain how external stimuli (promotions and discounts) influence consumer behavior through internal mechanisms (Brand Trust). A quantitative method with a cross-sectional design was used, involving 377 respondents selected through purposive sampling. Data were collected via questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results show that event promotions significantly and positively affect impulse buying, while price discounts do not have a statistically significant direct effect. However, Brand Trust significantly influences impulse buying and acts as a mediating variable in the relationships between both promotional events and price discounts with impulse purchases. These findings indicate that while promotions alone can drive unplanned purchases, their impact is amplified when consumers already trust the brand. The study confirms that Brand Trust plays a vital role in enhancing consumer responsiveness to marketing strategies, particularly in health-focused FMCG products like Fitbar. The research concludes that building strong Brand Trust is essential for maximizing the effectiveness of promotional activities. Practically, marketers are encouraged to combine event-based promotions with efforts to strengthen consumer trust through education, sampling, and consistent brand messaging.